Implementation of Civil Servants Performance Management in The Mahakam Ulu Regency Government - Owena Mayang Shari Belawan; Fibria Indriati (Greenation Research & Yayasan Global Resarch National, 2025)
Civil servant performance plays a vital role in governance. Furthermore, under the decentralized system implemented in Indonesia, civil servants serve as the backbone of local governments. However, civil servant performance presents a problematic situation influenced by the implementation of performance management. Focusing on Mahakam Ulu regency, this study aims to analyse the implementation of civil servant performance management in the region. This is a qualitative study, with data collected through interviews and document studies. Using an illustrative data analysis method, the study demonstrates that the overall implementation of civil servant performance management in the Mahakam Ulu regency government, as seen from the dimensions of performance planning, performance monitoring and measurement, performance evaluation, and employee development, has been running procedurally in accordance with stages and regulations. Although the processes have been implemented and are generally considered effective, various challenges remain to be addressed to achieve optimal results.